Knowledge, attitude, response of complementary and alternative medicine (CAM) among nursing students of faculty of medicine and health sciences, Universiti Malaysia Sabah - Sadia Choudhury Shimmi; M Tanveer Hossain Parash; Shaila Kabir (Malaysian Journal of Medicine and Health Sciences, 2020)
The National Centre for Complementary and Alternative Medicine (NCCAM) defines complementary and alternative medicine (CAM) as a group of diverse medical and health care systems, practices, and products that are not generally considered part of conventional medicine. Many types of CAM practices, and they may be grouped into categories such as natural products, mind–body, and body-based practices. A broad collection of own-care and practitioner-based practices, (CAM) has been a major stream health care to meet the primary health care needs of people for centuries. A good proportion of the world’s population, even in developed countries, continue to depend on CAM. This study aimed to find out the knowledge, attitude, and responses among nursing students of Faculty of Medicine and Health Sciences, Universiti Malaysia Sabah, Malaysia. Methods: This cross-sectional study was carried out between June 2015 and June 2016. One hundred and eight (108) nursing studentsparticipated by simple random sampling. After taking informed consents, data were collected by structured questionnaire. The first section of survey data contained demographic profille. The second, third and fourth sections of the survey instrument consisted of the items assessing the knowledge of, interest in, and attitudes toward CAM. The last section consisted items to assess the attitude towards the teaching-and-learning in the curriculum. Descriptive statistics were used to present the data. Results: Out of 108 students, there were 19 males and 89 females. Knowledge did not have any relation (p>0.05) to response towards CAM but both positive and negative attitude was significantly (p<0.001) related to the response. Conclusion: Changes in the attitude will increase the use of CAM as complementary to the modern medicine. This attitude change requires extensive scientific studies regarding usefulness, side effects, and mechanism of actions of CAM.